TANTANGAN DAN PENGUATAN IDEOLOGI PANCASILA DALAM MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 - Fadilah, Nurul (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2019)
The ideology of Pancasila as a way of life, the basis of the state, and national identity has a various challenge from time to time so that the existence of Pancasila as an Ideology must be maintained, especially in industrial revolution 4.0. The research method used is a qualitative approach by doing study of literature. In data collection the writer used documentation while in techniques data analysis used content analysis, inductive and descriptive. Results of the research about challenges and strengthening of the Pancasila Ideology in facing the era of the industrial revolution 4.0 are: (1) grounding Pancasila, (2) increasing professional human resources based on Pancasila’s values, (3) maintaining the existence of Pancasila as the State Ideology.